Methods of Planning Econometric Modeling of Communication and Information Services - Носиров Бахтиёр Нусратович (European Science Publishing, 2024)
The article discusses the service sectors, econometric models for the development of communication and information services for the population, in particular, methods of indicative planning of econometric modeling, and also makes proposals and recommendations based on the results obtained.
Keywords: service sector, econometric modeling, simulation model, communication and information services, economic calculations, static and dynamic parameters, synthesis, optimization, indicative planning, heuristic methods, economic and mathematical methods, regression equation.